A Polarization Programmable Antenna Array. (September 2022) - Chen, Dingzhao; Liu, Yanhui; Li, Ming; Guo, Pan; Zeng, Zhuo; Hu, Jun; Guo, Y. Jay
Abstract: Reconfigurable antennas are becoming a major antenna technology for future wireless communications and sensing systems. It is known that, with a single linear polarization (LP) reconfigurable antenna element, a preferred polarization can be produced from a set of multiple polarization states, thus improving the quality of the communication link. This paper presents a new concept of a polarization programmable reconfigurable antenna array that consists of a number of polarization reconfigurable antenna elements with a finite number of possible polarization states. By employing a new optimization strategy and programming the polarization states of all the array elements, we demonstrate that it is possible to realize any desired LP in the vectorial array radiation pattern with accurate control of sidelobe and cross-polarization levels (XPLs), thereby achieving the desired polarization to perfectly match that of the required communications signal. Both numerical and experimental results are provided to prove the concept, and they agree well with each other.